Analisis Hukum terhadap Notaris/PPAT yang Melakukan Penggelapan Pajak saat Peralihan Hak atas Tanah: Studi Putusan Nomor 57/Pid.B/2024/PN Mdn - Safirah Fathin Marini; Hasim Purba; Rosnidar Sembiring (CV Rewang Rencang, 2026)
Notaries are public officials authorized to draw up authentic deeds and sometimes assist clients in paying taxes related to such deeds. However, tax payment is not part of their legal authority. The absence of clear regulation regarding entrusted tax payments often leads to legal issues, including embezzlement. This study examines the legal responsibility of Notaries/PPAT in ensuring tax payments, the legal consequences of tax embezzlement, and judicial considerations in Decision No. 57/Pid.B/2024/PN Mdn. Using normative legal research, the findings show that misuse of entrusted tax funds may result in criminal, administrative, and ethical sanctions due to breach of trust and professional obligations.